2016
DOI: 10.1038/srep32886
|View full text |Cite
|
Sign up to set email alerts
|

Integrated stress response of vertebrates is regulated by four eIF2α kinases

Abstract: The integrated stress response (ISR) is a cytoprotective pathway initiated upon phosphorylation of the eukaryotic translation initiation factor 2 (eIF2α) residue designated serine-51, which is critical for translational control in response to various stress conditions. Four eIF2α kinases, namely heme-regulated inhibitor (HRI), protein kinase R (PKR), PKR-like endoplasmic reticulum kinase, (PERK) and general control non-depressible 2 (GCN2), have been identified thus far, and they are known to be activated by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
226
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(233 citation statements)
references
References 54 publications
(53 reference statements)
7
226
0
Order By: Relevance
“…Of note, impairment of eIF2α phosphorylation in response to kinases other than PKR was previously reported (36, 37). Consistently, DENV and ZIKV infection blocked eIF2α phosphorylation induced by treatment with arsenite, which activates both heme-regulated eIF2α kinase (HRI) and general control nonderepressible 2 (GCN2), thapsigargin, which activates the PKR-like endoplasmic reticulum kinase (PERK), and carbonyl cyanide p -(trifluoromethoxy) phenylhydrazone (FCCP), which activates HRI (61) (see Fig. S5A to F in the supplemental material).…”
Section: Resultsmentioning
confidence: 69%
“…Of note, impairment of eIF2α phosphorylation in response to kinases other than PKR was previously reported (36, 37). Consistently, DENV and ZIKV infection blocked eIF2α phosphorylation induced by treatment with arsenite, which activates both heme-regulated eIF2α kinase (HRI) and general control nonderepressible 2 (GCN2), thapsigargin, which activates the PKR-like endoplasmic reticulum kinase (PERK), and carbonyl cyanide p -(trifluoromethoxy) phenylhydrazone (FCCP), which activates HRI (61) (see Fig. S5A to F in the supplemental material).…”
Section: Resultsmentioning
confidence: 69%
“…Recent studies in fibroblasts lacking all four stress kinases (GCN2, PERK, HRI and PKR) has confirmed that no other kinases phosphorylate eIF2α (Taniuchi et al, 2016). However, the phosphorylation of eIF2α is countered by the Ppp1r15a/Gadd34 phosphatase, which terminates stress kinase signaling (Tsaytler et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, the phosphorylation of eIF2α is countered by the Ppp1r15a/Gadd34 phosphatase, which terminates stress kinase signaling (Tsaytler et al, 2011). We therefore isolated CD8 + T cells from GCN2 WT or GCN2 KO cells on an OTI background and measured p-Ser51 on eIF2α across time of stimulation using validated and highly specific mAbs (Taniuchi et al, 2016). We found p-Ser51 eIF2α in all samples at time zero, which may reflect stress from processing and purifying the T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four core stress activated kinases that phosphorylate eIF2α: Protein Kinase R (PKR), PKR-like/Pancreatic Endoplasmic Reticulum kinase (PERK), Heme-Regulated Inhibitor (HRI), or General Control Non-derepressible 2 (GCN) (Taniuchi et al, 2016). PKR is activated by double stranded RNA, enabling it to respond to viral infection (Taniuchi et al, 2016).…”
Section: Targeting Stress Granule Formation In Neurodegenerative Disementioning
confidence: 99%